Community Factors associated with Initiation to HPV Vaccination among Adolescent Girls aged 9 to 17 years in Eastern Uganda. A Cross-sectional Study - Wangwa, Fred (Student's Journal of Health Research Africa, 2022)
Background Initiation to the HPV vaccine is critical in the prevention of cervical cancer and failure to receive vaccines as recommended may aggravate the disease burden on the female population. Unfortunately, evidence indicates that initiation to HPV vaccination is still very low in Mbale district, Uganda, and sub-Saharan Africa at large. Hence this study was conducted to document the Community factors associated with the Initiation of HPV Vaccination among Adolescent girls aged 9 to 17 years in Eastern Uganda. Methodology: The study adopted a population-based cross-sectional study design in which questionnaires were used in the data collection process. The data were analyzed in STATA. Results: Family support and the caretaker’s average monthly income range were the factors that had a significant association with the initiation of HPV. The rest of the community factors did not show a significant association with initiation to HPV vaccination as they had p-values Conclusion: Community factors play a role in influencing caretakers towards initiation to HPV vaccination when assessed in isolation. Also, factors significantly influence the caretaker’s decision to initiate their adolescent girls to HPV vaccination. Recommendations Community health inspectors should adopt the role of sensitization about HPV vaccination against cervical cancer in adolescent girls within the recommended age range of 9 to 14 years as they perform their community health inspection roles.